2014
DOI: 10.4103/0019-5545.140649
|View full text |Cite
|
Sign up to set email alerts
|

Child who presented with hematohidrosis (sweating blood) with oppositional defiant disorder

Abstract: Hematohidrosis is a very rare condition of sweating blood. A child's case who presented to us with hematohidrosis is reported. There are only few reports in the literature. A 10-year-old boy presented to our hospital with a history of repeated episodes of oozing of blood from navel, eyes, ear lobules, and nose. During the examination, it disappeared as soon as it was mopped leaving behind no sign of trauma only to reappear within a few seconds. Bleeding time, clotting time, and prothrombin time were normal. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Bleeding in the mouth was reported three times; bleeding on the tongue was reported twice. Bleeding from multiple mucosae was reported in two patients (12,23), one of whom was found to have a platelet function defect (Platelet Factor 3, PF3 dysfunction) (12). An analysis of the bloody secretions was performed in 18 cases (72%), in two instances indirectly on clothes or tissues (11,22).…”
Section: Resultsmentioning
confidence: 99%
“…Bleeding in the mouth was reported three times; bleeding on the tongue was reported twice. Bleeding from multiple mucosae was reported in two patients (12,23), one of whom was found to have a platelet function defect (Platelet Factor 3, PF3 dysfunction) (12). An analysis of the bloody secretions was performed in 18 cases (72%), in two instances indirectly on clothes or tissues (11,22).…”
Section: Resultsmentioning
confidence: 99%
“…Cases occur mainly in young women, but both genders and a wide range of ages are present in the literature. The fluid is less viscous than blood but contains all of the cellular components that would be found in circulating blood 19 . The bloody fluid most often appears on the face or the hands, though it can occur from almost any body surface.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of bleeding and headache increased, and the boy was unable to attend school. We, therefore, initiated treatment with propranolol, a medication with known effect on migraine that also had been reported to have a positive effect on haematohidrosis . We started treatment with propranolol 1.8 mg/kg/day (20 mg × 3).…”
Section: Paediatric Cases Of Haematohidrosis 1970–2018mentioning
confidence: 99%
“…Skin biopsy was performed in nine cases, which were normal or showed nonspecific changes . In one study, the biopsies from a 14‐year‐old girl in 2008 showed dermal‐located, blood‐filled spaces that opened on the skin surface or in follicular canals; however, the cause of the spaces remained unclear . All children had been screened for coagulation disorders.…”
Section: Paediatric Cases Of Haematohidrosis 1970–2018mentioning
confidence: 99%